2004
DOI: 10.1093/intimm/dxh160
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional deficiencies of monocyte-derived dendritic cells in systemic lupus erythematosus (SLE) patients

Abstract: Systemic lupus erythematosus (SLE) represents an autoimmune disease for which alterations of T cells, B cells as well as various antigen-presenting cell (APC) populations have been described. In order to better define APC-associated deficiencies, we analyzed morphologic, phenotypic and functional characteristics of in vitro-generated monocyte-derived dendritic cells (MoDC) from SLE patients as compared with healthy controls. Analysis of MoDC at different stages of maturation revealed substantial phenotypic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 31 publications
5
39
1
Order By: Relevance
“…Confirming a previous study (54), no morphologic differences in the capacity of monocytes to differentiate into DCs were found between SLE and controls, using light and fluorescent microscopy ( Fig. 1).…”
Section: Myeloid Lupus Dcs Display Abnormal Levels Of Differentiationsupporting
confidence: 91%
“…Confirming a previous study (54), no morphologic differences in the capacity of monocytes to differentiate into DCs were found between SLE and controls, using light and fluorescent microscopy ( Fig. 1).…”
Section: Myeloid Lupus Dcs Display Abnormal Levels Of Differentiationsupporting
confidence: 91%
“…However, recent data obtained by Ding et al [17] and Decker et al [16] was more comparable to our findings. Different results in the more recent studies may have occurred due to younger DC populations (days 5-7 versus day 8 in the Koller et al study [14]), or maturation effects from the use of fetal bovine serum (FBS) to generate cells [26]. In addition, as shown in this study, a significant portion of patients may have iDC surface CD86 and MHC class II levels that are lower or comparable to those in healthy individuals.…”
Section: Discussionmentioning
confidence: 52%
“…This hypothesis is consistent with the accelerated AMLR and HMLR response seen in most SLE patients. Again, Koller et al [14] found an AMLR decrease in lupus patients. However, they used relatively ''old'' iDC that may have exhausted their extra maturation capacity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations